The Influence of Entrepreneurial Marketing and Government Policies on MSME Competitiveness (Study on Home Industry in Luwu Regency) - Sriwianti Firdaus; M. Risal (Jurnal Mantik, 2022)
The purpose of this study was to analyze the effect of entrepreneurial marketing and government policies on the competitiveness of SMEs in Luwu Regency. This study uses primary data, which was obtained by distributing questionnaires to respondents, in this case MSMEs in Luwu Regency, with a sample size of 78. To analyze the data of this study, multiple linear regression was used and processed with the SPSS application. The results of this study show that entrepreneurial marketing variables and government policies jointly affect the competitiveness of MSMEs in Luwu Regency. partially entrepreneurial marketing variables and government policies have a positive and significant effect on the competitiveness of MSMEs in Luwu Regency.